A subclass of harmonic meromorphic functions - Aini Janteng; Suzeini Abdul Halim (Hikari Ltd, 2007)
Complex-valued harmonic meromorphic functions that are univalent and orientation preserving outside the unit circle Ũ can be written in the form f = h + g, where h and g are analytic in Ũ. We define and investigate a subclass of harmonic meromorphic functions. We obtain coefficient conditions, extreme points, distortion bounds, convolution conditions and convex combinations for the above subclass of harmonic meromorphic functions.